AKREDITASI MADRASAH SEBAGAI KUNCI KEBERHASILAN DALAM PEMENUHAN STANDAR NASIONAL PENDIDIKAN (SNP) - Farida Hanun (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2015)
AbstractThis study aims to map the performance of Madrasah Aliyah, either has already or not yet accredited from the aspects of its education component and also to identify what are the the needs of madrasah in order to fulfill the accreditation criteria. The research on the requirements of Madrasah Accreditation use a survey method in 9 provinces (North Sumatra, Lampung, Riau, Banten, West Java, Central Java, East Java, South Sulawesi, NTB). The research showed that the fulfillment of the eight National Education Standards (NES) influence the quality of madrasah education and contribute to the success of accreditation. Directorate of Madrasah, Ministry of Religious Affairs provide guidance to madrasahs in accordance with its level of accreditation through a sustainable program  for  strengthening  Madrasah  in  the  field of managerial, human resources, facilities and infrastructure. AbstrakPenelitian ini bertujuan untuk memetakan performan Madrasah Aliyah yang sudah dan belum terakreditasi dari aspek standar Nasional Pendidikan (SNP) dan mengetahui apa yang menjadi kebutuhan madrasah dalam memenuhi kriteria akreditasi. Penelitian Studi Kebutuhan Akreditasi Madrasah menggunakan metode survey Madrasah Aliyah di 9 propinsi (Sumatera Utara, Lampung, Riau, Banten, Jawa Barat, Jawa Tengah, Jawa  Timur,  Sulawesi  Selatan,  NTB).  Hasil  penelitian menunjukkan pemenuhan delapan Standar Nasional Pendidikan (SNP) mempengaruhi peningkatan mutu penyelenggaraan pendidikan madrasah dan berkontribusi pada keberhasilan akreditasi. Direktorat Madrasah Kementerian Agama sebaiknya memberikan pembinaan kepada madrasah sesuai dengan jenjang akreditasi madrasah melalui program penguatan madrasah berkelanjutan di bidang manajerial, SDM, dan sarana prasarana.